2009
DOI: 10.1016/j.gaceta.2009.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Punto de corte óptimo de la concentración de cotinina en saliva para discriminar entre fumadores y no fumadores en la población adulta de Barcelona

Abstract: The optimal cut-point to discriminate smoking status in the adult population is 9.2 ng/ml, with sensitivities and specificities around 90%. The cut-point was higher in men and in younger people. The cut-point increases with higher prevalence of daily smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 28 publications
1
14
0
5
Order By: Relevance
“…Non-smokers were defined as individuals that, at the time of the interview, reported that they did not smoke, and they had a salivary cotinine concentration ≤10 ng/mL [17]. This group included individuals that had never smoked and ex-smokers.…”
Section: Methodsmentioning
confidence: 99%
“…Non-smokers were defined as individuals that, at the time of the interview, reported that they did not smoke, and they had a salivary cotinine concentration ≤10 ng/mL [17]. This group included individuals that had never smoked and ex-smokers.…”
Section: Methodsmentioning
confidence: 99%
“…En este sentido, la concentración de cotinina en saliva, aunque tiene una corta vida media y puede variar dependiendo del día de recogida, puede discriminar a partir de un determinado punto de corte a las personas que fuman de las que no fuman 18,20 . Además, la concentración de cotinina proporciona información sobre el riesgo individual de desarrollar enfermedad de las personas fumadoras 25,26 .…”
Section: Estrategia Individual Frente Al Tabaquismounclassified
“…La población diana de las intervenciones de "alto riesgo" serían las personas fumadoras. El punto de corte de la concentración de cotinina que discrimina la persona fumadora de la no fumadora en la población adulta española es de 10 ng/ml 20 . Las concentraciones de cotinina en suero (muy similares a las determinadas en saliva) superiores a 15 ng/ml se asocian positivamente con desarrollar un cáncer de pulmón 25,26 siendo las concentraciones de cotinina más elevadas las que tienen mayor asociación con un cáncer de pulmón.…”
Section: Estrategia Individual Frente Al Tabaquismounclassified
See 2 more Smart Citations